Detecção do vírus da hepatite e em suínos (Sus scrofa) e produtos processados derivados no estado de Mato Grosso, Brasil - Campos, Camila Gonçalves de (2022)
Hepatitis E is an emerging disease caused by the Hepatitis E Virus (HEV). As a result of zoonotic transmission, HEV is recognized in the concept of One Health and food safety. This thesis was divided into two articles. The first article used 25 samples of pig liver stored in paraffin blocks. These samples come from a published molecular detection and immunohistochemistry (IHC) study, which used the HEV ORF3 (pORF3) protein, showing 4% (1/25) immunostaining positive and 96% (24/25) negative. . In order to increase the sensitivity of the IHC technique, these samples were analyzed using the antibody for the detection of HEV ORF2 protein (pORF2), showing 24% (6/25) immunostaining positive and 76% (19/25) negative. Thus, the use of antibody to pORF2 increased the number of detectable HEV cases in the IHC by 600%. The second article used 58 samples of swine meat products acquired at different points of sale (municipal fairs and supermarket chains) in the city of Cuiabá/Mato Grosso, which were submitted to molecular examination in order to carry out viral detection in food products. All samples from fairs were negative for the presence of HEV RNA. In relation to supermarkets, 2 pâtés (2/7) were positive in the molecular test (28.5%). Thus, the first article demonstrated that IHC using a monoclonal antibody to HEV pORF2 added to molecular techniques can be used to improve the accuracy of viral detection, improving the diagnosis of sentinel animals and monitoring the circulation of HEV. The second work reinforced that processed meat products derived from swine may represent a source of HEV infection, reinforcing the need for monitoring swine herds, aiming to prevent zoonotic transmission of HEV to human populations in the CentralWest region of Brazil.